Bioprosthetic mitral valve stenosis secondary to hypereosinophilic syndrome. Issue 4 (26th February 2022) - Quan, Xin; Song, Yunhu; Wang, Hongyue; Yang, Sun; Zhu, Zhenhui
Abstract: Herein we present a case of hypereosinophilic syndrome (HES) with recurrent involvement of mitral valve. The patient developed mitral regurgitation secondary to HES. Surgical mitral valve replacement was performed successfully. The prosthetic valve dysfunction occurred 3 years later and echocardiography showed severe mitral valve stenosis. Extensive mural thrombi were discovered on both sides of the stenotic valve with eosinophilic infiltration. The patient underwent a repeated mechanical prosthesis replacement and recovered uneventfully.